CLINICAL PRESENTATION OF HYPOTHYROIDISM: A CASE CONTROL ANALYSIS - Khurram, Irfan M.; Choudhry, Kiran S.; Muhammad, Khan; Islam, Najmul (Journal of Ayub Medical College Abbottabad, 2003)
Background: Hypothyroidism is a common endocrinological disorder. Its clinical presentation is variable but well established. However, clinical features vary significantly among different populations owing to their climate, education status and awareness about the disease. This study is designed to evaluate the difference in clinical presentation of our population from already available literature. Methods: In this study we have compared the symptoms and signs of hypothyroid and euthyroid patients coming to a diagnostic centre (PINUM, Faisalabad) from January to July 1999. Of the 1594 patients coming to the centre, 394 were included in the study and were examined. After the laboratory investigations, 109 were identified as the cases of hypothyroidism, the rest were declared as euthyroid and selected as controls. We compared the 21 common signs and symptoms of hypothyroidism in our patients. Results: Lethargy was the commonest symptom and facial oedema was the most prevalent sign in our population. Old age is reported to be a risk factor for hypothyroidism but in this study we could not find a rising trend with increasing age (odds ratio 1.15, p-value 0.71). We also compared the clinical presentation of our patients with the available literature. It was also proved that the signs elicited by the physicians were more reliable and specific for the identification of hypothyroidism. Conclusion: Thus, the presentation of hypothyroidism is non-specific and high degree of suspicion is required for its early diagnosis. KEY WORDS: Hypothyroidism, Age Groups, Signs and Symptoms, Case-Control Studies.